HERPESVIRUS INFECTIONS IN CHILDREN WITH RECURRENT RESPIRATORY DISEASES - M. Yu. Lysenkova; N. V. Karazhas; E. V. Melekhina; T. N. Rybalkina; P. A. Veselovsky; E. M. Burmistrov; R. E. Boshyan; A. D. Muzyka; A. V. Gorelov (LLC "Diagnostics and Vaccines", 2018)
The article presents the role of herpesviral infections caused by the herpes simplex virus (HSV), the Epstein-Barr virus (EBV), cytomegalovirus (CMV) and human herpesvirus type 6 (HHV-6) in 36 children with recurrent respiratory tract diseases at the age from 1 to 18 years. Blood sera and blood cells were studied using ELISA, Indirect reaction of immunofluorescence and Rapid culture method.It was found that all 36 children (100%) were infected with HSV, EBV, CMV and HHV-6. Most often - in 19 children (52.8%) the signs of active HHV-6 were revealed. In the same number of children surveyed, it was possible to identify active EBVI (16 children - 44.4%) and CMVI (16-44.4%). Active HSVI was diagnosed in 13 children (36.1%). Herpes virus infections were most often detected in the age group of children from 3 to 7 years of age.All children with recurrent respiratory diseases should be examined for herpesvirus infections.